Development of Electrohydraulic Proportional Valve Model for Precise Steering Control in Autonomous Tractors - Yi-Seo Min; Yong-Joo Kim; Seung-Yun Baek; Seung-Min Baek; Wan-Soo Kim (Machines)
Autonomous tractors are emerging as a pivotal technology in agricultural automation. Precise steering control in these tractors requires high-performance electrohydraulic proportional valves (EHPVs). To optimize EHPV performance and reduce development costs and time, simulation analysis serves as a valuable pre-testing tool. This study aimed to develop a simulation model capable of predicting the hydraulic characteristics of EHPVs under real-world operating conditions. The model was created using AMESim, incorporating actual tractor operating conditions and valve control signals. The proposed model was validated through experiments conducted on a tractor equipped with an EHPV, evaluating hydraulic characteristics across various engine speeds and steering angular velocities. The simulation model was utilized to analyze the priority valve control flow characteristics of the automatic steering system and the hydraulic response of the EHPV under step inputs at specific engine speed points. The results indicate that the simulation model demonstrated a mean absolute percentage error (MAPE) ranging from 7.45% to 9.79% for hydraulic power. A t-test analysis of hydraulic power indicated no statistically significant difference between the simulation and experimental values under all test conditions. The proposed EHPV simulation model can be utilized for the optimal future design of EHPV systems.